Assessment of parasite clearance following treatment of severe malaria with intravenous artesunate in Ugandan children enrolled in a randomized controlled clinical trial - Byakika‑Kibwika, Pauline; Nyakato, Patience; Lamorde, Mohammed; Kiragga, Agnes N. (Malaria journal, 2018)
Worldwide, malaria ranks as one of the most important causes of morbidity and mortality with 216 million cases and 445,000 deaths in 2016 alone, 90% of cases and deaths occur in Africa and 80% in sub-Saharan Africa Uganda is one of the heavy malaria burden countries where Plasmodium falciparum, which causes the most severe form of disease is the most prevalent [1]. Malaria is transmitted by the female Anopheles mosquito which injects sporozoites into the human host. Sporozoites undergo pre-erythrocytic and erythrocytic stages of multiplication causing erythrocyte rupture with release of merozoites and pro-inflammatory cytokines into circulation, which are responsible for the symptoms. Patients seek medical attention when they begin to experience symptoms of malaria.
Keywords: Artesunate; ACT; Malaria; Parasite clearance